ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INFLASI DI INDONESIA PERIODE 2000.1-2011.4 - Primawan Wisda Nugroho; Maruto Umar Basuki (Universitas Diponegoro, 2012)
One of the problems that often occur in developing countries in implementing the country's development is how to maintain stability and economic growth. Economic stability in terms of stability regarding the price level, the level of national income and employment growth. The main objective of this study was to analyze the factors affecting inflation in Indonesia in 2000.1-2011.4 period. The variables used are: gross domestic product (GDP), the money supply in a broad sense (M2), interest rate, Bank Indonesia certificates (SBI), and the exchange rate of rupiah against the U.S. dollar. The data used in this study is time series data in the quarterly period from 2000.1 to 2011.4, using multiple linear regression with the method of Ordinary Least Square (OLS). The results of this analysis states that the variable gross domestic product and the SBI rate are positive and significant effect on inflation. While exchange rate are positive and not significant effect on inflation. In the other hand, the variables in the money supply (M2) is negative and significant effect on inflation in the quarter a year of research.